Examining the Link between Innovation, Productivity and Growth: a Global View - Marinko Škare; Daniel Tomic (Amfiteatru Economic Journal, 2014)
Innovation has long been recognized as one of the key elements of economic progress, though some say that its direct relation to the concept of economic growth remains rather controversial. Productivity growth is the key economic indicator of innovation, non-the-less. Growth theory assumes that changes in real output are result of technological shocks within the economy. Using ARIMA modelling techniques and Beveridge-Nelson univariate decomposition this paper estimates the impact of technological shocks on GDP, GDP per capita and labour productivity (long-term) growth of OECDs' most developed countries. The study explores the global effects of the 'third industrial revolution' for 25 OECD countries over 1950-2013 periods. The impact of innovations on growth differs in intensity and time among the countries. Measured impact of technological innovation on growth is significant, and it is expected to become even more significant in the future. Economic growth is riding on the technological innovation wave but for how long and how far it is uncertain if the 'Great Decoupling' problem is to abound. Positive impact of technological innovation on growth and welfare is seriously risked by the high divergence and inequality arising from the Great decoupling problem.
Keywords: O30; O32; O33; O37; O38; 330; computer and information technology; productivity and growth; ARIMA models; Beveridge-Nelson decomposition; OECD countries